Leaf burn on sprinkled citrus: Factors affecting leaf absorption of sodium and chloride from water sprinkler-applied to citrus and avocados studied - R Harding; M Miller; M Fireman (California Agriculture, 1957)
Leaf burn and defoliation on the lower part of the tree found in the fall of 1955 in several citrus orchards in Riverside County—recently converted to the lowhead type of sprinkler irrigation—led to a preliminary survey of citrus and avocado orchards in the county. Leaf burn on the skirts of sprinkled citrus orchards was found in the Hemet, La Sierra, Corona, and Coachella Valley areas. Varieties included grapefruit, Valencia and navel orange, and tangerine. Sprinkled avocado orchards did not show the marked burn on the tree skirts found in citrus. In some cases, a white salt residue was found on the citrus leaves on the portion of the tree that was wetted during sprinkling. The upper part of the tree which received no water spray during irrigation showed no burn or defoliation.